ISI spectral radii and ISI energies of graph operations - Bilal, Ahmad; Munir, Muhammad Mobeen; Qureshi, Muhammad Imran; Athar, Muhammad (Frontiers in Physics, 2023)
Graph energy is the sum of the adjacency matrix's absolute eigenvalues. The graph's spectral radius represents the adjacency matrix's largest absolute eigenvalue. Applications for graph energies and spectral radii can be found in both molecular computing and computer science. This article's main focus is the Inverse Sum Indeg, ($ISI$) energies, and ($ISI$) spectral radii of the $p$-splitting and $p$-shadow graphs constructed on any regular graph. Only the comparison of the energies and spectral radii of the newly created graphs to those of the base graph may be questioned. Concentrating on these two graph operations, we compute new relations between the $ISI$ energies and spectral radius of the new graph with the original graph.